Effect of Herbicides on Weed Control and Seed Yield Parameters in Coreopsis lanceolata - G. S. BADHESHA; RAMESH KUMAR; K.K. DHATT; S. SINGH (Seed Research, 2026)
The studies were undertaken at PAU Ludhiana during 2001-2002 on Coreopsis lanceolata to find out effective herbicide with optimum concentration. Fluchloralin, trifluralin @0.75 kg/ha, 1.0 kg/ha, @0.75 kg/ha + 2 hand weeding at 45 and 90 days of transplanting and pendimethalin @ 0.50 kg/ha, 0.75 kg/ha, @0.50 kg/ha + 2 hand weeding at 45 and 90 days of transplanting were sprayed two days prior to transplanting. These treatments were also compared with unweeded treatment and hand weeded plot at 15 day interval throughout the period of experiment. Pendimethalin @0.50 kg/ha + 2 hand weeding was found to be the best control measure in terms of weed population, of weed population, weed fresh and dry matter. Hand weeded treatment resulted in maximum plant height (85.18 cm), plant spread (68.93 cm),branches (22.89/plant) and the longest flowering duration (51.5 days). Fluchloralin @0.75 kg/ha + 2 hand weeding resulted in maximum seed yield 62.87 g/m³ followed by pendimethalin @ 0.50 kg/ha + 2 hand weeding. Seed germination was recorded highest (79%) under hand weeded plot which was closely followed by fluchloralin @ 0.75 kg/ha + hand weeding. The weed population of 111.25/m² and 113.56/m² was recorded due to fluchloralin @0.75 kg/ha and pendimethalin @0.50kg/ha respectively.